Rice near-isogenic-lines (NILs) contrasting for grain yield under lowland drought stress - Venuprasad, R.; Impa, S.M.; Veeresh Gowda, R.P.; Atlin, G.N.; Serraj, R. (Elsevier, 2011)
The development of near-isogenic-lines (NILs) is a very important tool for both genetic and physiological dissection of drought resistance in rice. Two pairs of NILs differing for grain yield under drought stress were isolated and characterized for yield, yield related traits, and several physiological traits in a range of contrasting environments. In replicated field trials both NIL pairs differed significantly for grain yield under drought stress but showed similar yield potential, phenology, and yield component traits under non-stress conditions. A polymorphism analysis study with 491 SSRs revealed that both NIL pairs are at least 96% genetically similar. These NILs show that small genetic differences can cause large difference in grain yield under drought stress in rice. In both pairs the drought-tolerant NILs showed a significantly higher assimilation rate at later stages both under stress and non-stress conditions. They also had a higher transpiration rate under non-stress condition. The most tolerant NIL (IR77298-14-1-2-B-10) had significantly higher transpiration rate and stomatal conductance in severe stress conditions. In one pair the tolerant NIL had constitutively deeper roots than the susceptible NIL. In the second pair, which had higher mean root length than the first pair, the tolerant NIL had more roots, greater root thickness, and greater root dry weight than the susceptible NIL. Deeper root length may allow tolerant NILs to extract more water at deeper soil layers. It is concluded that enhanced rooting depth is an important strategy for dehydration avoidance and rice adaptation to drought stress, but root architecture might not be the only mechanism causing the significant yield increase we observed in lowland drought stress environments. To further dissect the drought avoidance mechanisms in rice, analysis of root hydraulic properties may be necessary.